Investigating process stresses on Saccharomyces cerevisiae using isothermal microcalorimetry - Myers, Matthew (Centre for Bioprocess Engineering Research, 2017)
Maximising performance of microbial processes, including yeast-based processes, in an industrial setting requires understanding of the impact of process stresses. These may be the result of process configuration, dilution, temperature changes, hydrodynamic conditions or process perturbations. Methods to determine the microbial metabolic response to such stresses have long been sought, but are typically limited, often requiring the use of a suite of methods to assess the physiological status and state. The recent technical advances in microcalorimetry suggest potential for the use of isothermal microcalorimetry (IMC) to determine yeast viability and vitality and is investigated here. IMC is a laboratory method whereby the real-time heat produced by a chemical, biological or physical process is measured in the micro to nano watt range. It is proposed that this heat production may be correlated to the physiological state of the microbial catalyst and can be used to measure the impact of different stresses. In this study, the potential of IMC as a method for exploring process stress is investigated using Saccharomyces cerevisiae and its application in the beer brewing industry as a case study. Here, it is well known that yeast viability and vitality have commercial significance. IMC is sufficiently sensitive to detect the heat given off by 1000 yeast cells. However, IMC cannot distinguish between different heat flows within a system i.e. it is non-specific. The literature demonstrates how IMC has been used in the study of numerous microbiological fields, including the growth and metabolism of yeast. Previous studies have successfully derived the specific growth rate and cell numbers of a growing yeast population from analysing power and heat curves. The specific growth activity and specific growth retardation of yeast and how these parameters relate to bactericidal and bacteriostatic effects has also been examined by a number of authors. The key objectives of this study were to determine the viability and vitality of Saccharomyces cerevisiae using IMC and to assess the impact of stresses on yeast viability and vitality. This was achieved by measuring the thermal power produced by a growing yeast suspension as a function of its overall growth and metabolism. Two industrially relevant stresses were examined: cold shock and ethanol shock. The effect of these stresses has yet to be studied using microcalorimetry. The growth of Saccharomyces cerevisiae under ethanol stress was used as an inhibition study to isolate its effects on the growth thermogram. Following the generation of thermograms under control and stress conditions using IMC, a method for their quantitative analysis was developed. Curves were fitted to the heat data using an exponential growth equation and the time for the heat flow curve to peak was determined. From the exponential curve, the specific growth rate of the yeast was determined with a high degree of repeatability. The coefficient of the exponential term in the growth equation gave highly reproducible and distinguishable results relating to the viability and vitality of the initial yeast population. The time of peak heat flow was also affected by the initial viability and vitality of the yeast and was used to estimate the initial active cell population size.